Comparative Studies on the Proximate Composition of the Various Body Part of Clarias gariepinus and Scomber scomrus - K.U. Ogbe; O.I. Omada (Journal of Applied Sciences and Environmental Management, 2020)
Study on the proximate a composition of flesh and other body parts of Clarias gariepinus and scomber scombrus was carried out in January, 2020  using standard procedures. For Clarias gariepinus the highest protein (25.69%) was observed in the head, followed by flesh (21.70%) and while the  lowest protein (18.61%) was discovered in the bone. Highest fats (3.61%) was recorded in the flesh, followed by head (2.25) while (0.80%) recorded in the fins as the lowest fats. In fibre the highest (1.87%) was observed in head followed by (1.72) in the bone. The lowest fibre (0.60%) was reported in the flesh. The highest ash (22.03%) was recorded in fins, followed by bone (19.83%) while the lowest (1.30%) was discovered in the flesh. The highest moisture (75.76%) was recorded in the flesh, followed by fins (73.23) while the lowest (56.48%) was observed in the head. For scomber scombrus the highest protein (29.44%) was observed in the head, followed by bone (28.40%) and while the lowest protein (24.30%) was discovered in the flesh. Highest fats (6.42%) was recorded in the flesh, followed by head (1.48%) while (0.95%) recorded in the bone as the lowest fats. In fibre the highest (1.11%) was observed in fin followed by (0.69%) in the flesh. The lowest fibre (0.59%) was reported in the head. The highest ash (6.37%) was  recorded in  head, followed by bone (5.07%) while the lowest (0.33%) was discovered in the flesh .The highest moisture (68.68%) was recorded in the flesh, followed by head (66.56%) while the lowest (37.20%) was observed in the fin. .The highest carbohydrate (5.58%) was recorded in the bone, followed by fin (5.28%). The study showed that the best body parts in terms protein content of the two fish samples were the head. The Head has the highest crude protein content thus it can be recommended as a possible effective ways to solve protein malnutrition